Antibacterial Activity of Ballota acetabulosa Against Methicillin-Resistant Stapylococcus aureus - Dulger, Basaran; Ali Kilcik, Mehmet (Asian Journal of Chemistry, 2010)
Aqueous and ethanolic extracts obtained from Ballota acetabulosa (L.) Benth. (Lamiaceae) used as traditional medicine in Turkey have been investigated for their ability to inhibit 35 hospital isolates of Methicillin-resistant Staphylococcus aureus (MRSA). Both aqueous and ethanolic extracts were shown antimicrobial activity against MRSA isolates. The minimum inhibitory concentration (MIC) values of the ethanolic extract with the greatest antibacterial effect were those of the plant MIC 0.4-1.6 μg/mL and MBC 3.2-12.5 μg/mL, respectively.